A Comparative Study of Distillery Spent Wash with NPK (Standard Chemical Fertilizers) at Seedling Stage of Sorghum (Sorghum Bicolor L.) - Soomro, Aijaz Ahmed; Soomro, Ayaz Ahmed (Asian Journal of Agriculture and Rural Development, 2015)
The price of commercial chemical fertilizers is beyond the purchasing power of farming community of world’s developing countries. Therefore, to find out the substitute of these commercial chemical fertilizers a comparative study was conducted at seedling stage of sorghum variety named Sarokartuho in seed testing laboratory. The experiment was carried out in completely randomized design (CRD) with three replications and three treatments, i.e. only drinking water (as check), recommended dose of Nitrogen, Phosphorus, Potassium (NPK commercial fertilizer), 30%+70% of distillery spent wash + water, 50%+50% distillery spent wash + water respectively. The results for spent wash (T2) were at seed germination% (95.33%), shoot length (6.62 cm), root length (5.49 cm), shoot fresh weight (0.18 mg), root fresh weight (0.019 mg), shoot dry weight (0.017 mg) and root-dry weight (0.005 mg) of sorghum. However, the maximum values for these all traits of observations except seed germination were recorded at recommended dose of NPK (chemical fertilizers).